Consequences of 50,000 units of vitamin D during pregnancy: A review article - Farahnaz Rostami; Sedigheh Hantoushzadeh; Lida Moghadaam Banaem (Mashhad University of Medical Sciences, 2018)
Introduction: Vitamin D deficiency is associated with maternal and fetal complications; accordingly, it is of significant importance to investigate the treatment of this deficiency. There is still no clear optimal protocol for the treatment of vitamin D deficiency or for the proper dose of this supplementation and its effects on mothers and infants, which has led to controversies about the safety and effectiveness of vitamin D supplements during pregnancy. Despite the importance of this issue, there are few studies addressing high doses of vitamin D, such as 50,000 units of vitamin D3.Therefore, this systematic review aimed to investigate the effects of 50,000 units of vitamin D on pregnant women. Methods: This systematic review was performed on the Persian and English articles reporting the effect of vitamin D on pregnant women published during 2010-2017. The search process was accomplished through searching databases, such as PubMed, Science Direct, IranMedex, and Irandoc using the keywords of vitamin D in pregnancy, vitamin D deficiency, and clinical trials. In the initial search, 8648 articles were found; however, after employing the inclusion and exclusion criteria 8 articles were under the investigations.  Results: Studies were conducted on a total of 2011 pregnant women, out of whom approximately 992 received 50,000 units of vitamin D. In these studies, high dose of vitamin D had a significant relationship with the increase of maternal serum levels and the decrease in the maternal and neonatal complications, which included lower level of gestational diabetes,  reduction of premature labor, and increase of baby weight, compared to mothers with vitamin D deficiency. Conclusion: The 50,000 units of vitamin D in pregnant mothers with vitamin D deficiency increases serum level, compared to lower doses of vitamin D. This dose can be considered as a safe dose both for mothers and neonates.